2011
DOI: 10.1007/s11357-011-9315-4
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and age-related downregulation of Klotho in rhesus monkey

Abstract: While overall DNA methylation decreases with age, CpG-rich areas of the genome can become hypermethylated. Hypermethylation near transcription start sites typically decreases gene expression. Klotho (KL) is important in numerous age-associated pathways including insulin/IGF1 and Wnt signaling and naturally decreases with age in brain, heart, and liver across species. Brain tissues from young and old rhesus monkeys were used to determine whether epigenetic modification of the KL promoter underlies age-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 61 publications
5
60
0
6
Order By: Relevance
“…Since uremic toxins are believed to act via inflammatory pathways and we see evidence of neuroinflammation in our system, it is quite possible that elevated promoter methylation underlies the decreased brain α-Klotho seen in nephrectomized rats. Supporting this idea further, kl promoter methylation can be modulated in the brain, since an age-dependent increase that correlates with decreased protein expression has been reported in the white matter of rhesus monkeys (King et al, 2012). Altered promoter methylation in the brains of our animals is clearly a hypothesis that can be tested relatively easily.…”
Section: How Does Kidney Damage Cause Loss Of α-Klotho In the Brain? supporting
confidence: 71%
See 2 more Smart Citations
“…Since uremic toxins are believed to act via inflammatory pathways and we see evidence of neuroinflammation in our system, it is quite possible that elevated promoter methylation underlies the decreased brain α-Klotho seen in nephrectomized rats. Supporting this idea further, kl promoter methylation can be modulated in the brain, since an age-dependent increase that correlates with decreased protein expression has been reported in the white matter of rhesus monkeys (King et al, 2012). Altered promoter methylation in the brains of our animals is clearly a hypothesis that can be tested relatively easily.…”
Section: How Does Kidney Damage Cause Loss Of α-Klotho In the Brain? supporting
confidence: 71%
“…Some studies of α-Klotho gene expression have been reported, indicating that the kl promoter can be activated by testosterone and the androgen receptor (Hsu et al, 2014), and by the transcription factor Egr-1 (Choi et al, 2010). Perhaps most intriguingly however, α-Klotho transcription is strongly repressed by promoter methylation (Azuma et al, 2012;King et al, 2012;Sun et al, 2012). This phenomenon has been suggested to underlie the tightly controlled tissue-specific pattern of α-Klotho expression (Azuma et al, 2012) and is reported to increase with age (King et al, 2012).…”
Section: How Does Kidney Damage Cause Loss Of α-Klotho In the Brain? mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, pyrosequencing requires multiple sequencing primers and Sanger sequencing traditionally required cloning of PCR products, a laborious task (Zhang et al 2009). Nevertheless, these techniques have been used to great effect to generate base-specific analysis of selected regions and changes in methylation, but not hydroxymethylation, with aging (Noer et al 2007;Maegawa et al 2010;King et al 2012). …”
Section: Base-specificity Of Dna Modificationsmentioning
confidence: 99%
“…Additionally the validation approach used can be a model for qualification of other capture probe sets developed in the future. An exciting future direction of BOCS methodology in general will be the application of this technology to other important animal models in biomedical research, such as non-human primates (King et al 2012) and mice, which have been established as important model systems for disease research in the areas of neuroscience, substance abuse, and aging.…”
Section: Rat Genome Methylation Analysismentioning
confidence: 99%